Pengaruh Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Samsat Kabupaten Maros - Ansar; Andi Irwan; Amiruddin; Aminah; Fausiah (STIM-LPI Makassar, 2023)
The analytical method used in this study is multiple linear regression analysis, T test, F test, correlation analysis and determination. The results showed that the work environment hypothesis on employee performance was rejected on the basis of a calculated T value of 0.615 which was less than the T table value of 1.67203. In addition, the organizational culture hypothesis on employee performance was accepted on the basis of a calculated T value of 1.733 which was greater than the T table value of 1.67203. then the results of the correlation coefficient test show that the work environment and organizational culture have a low relationship to employee performance. Then, based on the results of the Determination test, it shows that the contribution of the work environment and organizational culture is 14.9% to employee performance variables.